Pengembangan Kemampuan Sosial Emosional Anak Usia Dini Melalui Kegiatan Bermain Peran - Fareza Taris Adinda Veolena Ramadhanti; Hirlita Anggrayani; Tika Puspita Sari; Intan Ria Juwita; Nurul Fauziah (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
Social-emotional skills are an important aspect of early childhood development that influences learning readiness and character formation. This study aims to analyze the role of role-playing activities in supporting children's social-emotional development. The method used is descriptive qualitative with a literature study approach through a review of accredited journals, early childhood education books, and articles published in the last five years. The results of the study show that role-playing can improve empathy, cooperation, emotional regulation, and communication. Children who are involved in this activity are more courageous in expressing themselves, understanding the feelings of others, and learning to control their emotions in social interactions. These findings confirm that role-playing not only serves as a means of entertainment but also as a learning strategy that supports the achievement of early childhood education learning in the Merdeka Curriculum. The implication of this research is the need for teachers to be creative in designing contextual role-playing scenarios, providing adequate playing facilities, and supporting educational policies so that role-playing activities can become the foundation for the formation of early childhood character that is empathetic, communicative, and disciplined.